Content and meaning of national law in the context of transnational law - Snijders, H; Vogenauer, S (Sellier European Law Publishers GmbH, 2009)
This collection of essays by Dutch, English, and Swiss scholars deals with the impact of transnational law, in particular the law of the European Union and the Council of Europe, on the content and meaning given to domestic law by national legislators and judges. The topics covered include the constitutional and practical implications of implementing transnational law at the national level; the interpretation of domestic law against the background of the European Convention on Human Rights; the law of the European Union; and so called "soft law" instruments in areas, such as civil procedure, jurisdiction, contract, company law, and competition law.